Marine navigation : proceedings of the 12th International Conference on Marine Navigation and Safety of Sea Transportation (TransNav 2017), June 21-23, 2017, Gdynia, Poland /: proceedings of the 12th International Conference on Marine Navigation and Safety of Sea Transportation (TransNav 2017), June 21-23, 2017, Gdynia, Poland. (2017) - Unknown
No abstract available